2021
DOI: 10.1002/2211-5463.13253
|View full text |Cite
|
Sign up to set email alerts
|

Rondonin: antimicrobial properties and mechanism of action

Abstract: Infectious diseases are among the major causes of death in the human population. A wide variety of organisms produce antimicrobial peptides (AMPs) as part of their first line of defense. A peptide from Acanthoscurria rondoniae plasma, rondonin -with antifungal activity, a molecular mass of 1,236 Da and primary sequence IIIQYEGHKH -was previously studied (Uniprot accession number B3EWP8). It showed identity with the C-terminus of subunit "D" of the hemocyanin of the Aphonopelma hentzi spider. This result led us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 107 publications
(151 reference statements)
3
13
0
Order By: Relevance
“…In a recent work, we demonstrated that the arthrodial membrane of the harvester Mischonyx squalidus (Arachnida, Opiliones) shows features of secretory activity such as pores and cuticular canals, secretory cells with mitochondria, smooth endoplasmic reticulum and secretory granules [Silva et al 2021, unpublished data]. Furthermore, we demonstrated that the secretions of these secretory cells include proteins and oils [Silva et al 2021]. In view of this evidence and based on the literature, we suggest that the arthrodial membrane has a gland with a lubricating function at least in the studied leg joint of leg IV [Silva et al 2021, unpublished data].…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…In a recent work, we demonstrated that the arthrodial membrane of the harvester Mischonyx squalidus (Arachnida, Opiliones) shows features of secretory activity such as pores and cuticular canals, secretory cells with mitochondria, smooth endoplasmic reticulum and secretory granules [Silva et al 2021, unpublished data]. Furthermore, we demonstrated that the secretions of these secretory cells include proteins and oils [Silva et al 2021]. In view of this evidence and based on the literature, we suggest that the arthrodial membrane has a gland with a lubricating function at least in the studied leg joint of leg IV [Silva et al 2021, unpublished data].…”
Section: Introductionsupporting
confidence: 50%
“…The proteomic analysis of the content of the secretory cells in the AM revealed similarities with proteins, speci cally with peptides with antimicrobial activity [Silva et al 2021], whose activity has now been demonstrated. Moreover, both fractions have antimicrobial activity at low concentrations, which is important from a pharmacological point of view (Nascimento et al 2016;Diniz et al 2018;Diaz-Roa et al 2018, 2019.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…PR-39, an AMP isolated from the upper half of the pig's small intestine, kills bacteria by preventing the synthesis of proteins and DNA and causing the degradation of these components [116]. Other AMPs that can interact with nucleic acids include human neutrophil peptide (HNP)-1 [117], porcine β-defensin 2 (pBD2) [118,119] and rondonin [120];…”
Section: Amps Acting On Intracellular Targetsmentioning
confidence: 99%